PENGARUH JUMLAH PENUMPANG KERETA API TERHADAP TOTAL PENDAPATAN STASIUN PEKALONGAN BULAN JANUARI – APRIL 2020 - Muhammad Iqbal Notoatmojo; Rizka Ariyanti; Naila Fitriani (Politeknik Negeri Semarang, 2020)
The purpose of this study was to determine the effect of the number of passengers on the Kaligung train and the number of passengers on the Kamandaka train on the total revenue of Pekalongan Station in January - April 2020. This research is a research with a quantitative approach. The variables in this study consist of the number of passengers on the Kaligung train, the number of passengers on the Kamandaka train and the revenue for the Pekalongan Station. The population in this study were train passengers at Pekalongan Pekalongan Station. The sample in this study is the number of passengers of the Kaligung and Kamandaka trains. Data collection techniques with observation are to collect data on the number of passengers using the train with the RTS 4.0 application owned by PT Kereta Api Indonesia and analyzed using the classical assumption test and multiple linear regression test with SPSS software. for windows version 22. The conclusions of this study are: (1) The number of passengers of the Kaligung train has a significant effect on the revenue of Pekalongan Station. (2) The number of passengers on the Kamandaka train has no significant effect on the revenue of Pekalongan Station. (3) The number of passengers of the Kaligung and Kamandaka trains has a simultaneous effect on the revenue of Pekalongan Station.